Recent advances: peptides and self-assembled peptide-nanosystems for antimicrobial therapy and diagnosis. (28th July 2020) - Zou, Pengfei; Chen, Wen-Ting; Sun, Tongyi; Gao, Yuanyuan; Li, Li-Li; Wang, Hao
Abstract : Bacterial infections, especially the refractory treatment of drug-resistant bacteria, are one of the greatest threats to human health. Self-assembling peptide-based strategies can specifically detect the bacteria at the site of infection in the body and kill it. Abstract : Bacterial infections, especially the refractory treatment of drug-resistant bacteria, are one of the greatest threats to human health. During the past decades, biomedical nanomaterials have been developed in an increasing number of fields, which significantly contribute to our public healthcare systems. Peptide-based drugs, such as antimicrobial peptides, cyclopeptides, and glycopeptides, play important roles in the treatment of drug-resistant bacterial infections, due to their unique lower resistance antibacterial mechanism. Among them, biomimetic nanostructures fabricated by self-assembled peptide nanomaterials have received considerable development in surface protection, tissue engineering, bactericides, etc . Besides, bacterial diagnostic reagents based on self-assembled peptide materials also provide strong support for early detection and infection imaging of bacterial infections. In this review, we have systematically discussed peptide-based self-assembled nanomaterials, including their sequences, subunits, secondary structures, assembled nanostructures, and biomedical applications for antibacterial therapy and diagnosis. We have reviewed and discussed the structure–function relationship, molecular design strategy, and structure effect of antimicrobial peptides. The sequence design of self-assembled peptides and the application of self-assembled peptide nanomaterials in the diagnosis and treatment of bacterial infections are emphasized. Also, we analyzed and summarized the design and development of smart materials, reviewed the innovative " in vivo self-assembly" nanotechnology, and proposed the future design and prospect of smart self-assembly nanomaterials based on peptides in the biological antibacterial field.